Three essays in industrial organization: alliances, mergers, and pricing in commercial aviation - Brown, David R. (Kansas State University, 2010)
My research focuses primarily on industrial organization and applied microeconomics. Specifically, I have extensively studied the airline industry. My first essay considers the effect of the Delta/Continental/Northwest codeshare alliance. Codeshare agreements can benefit airlines due to network expansion and benefit consumers by eliminating a double markup on flight itineraries with multiple operating carriers. However, policymakers have expressed concern that an alliance between airlines may facilitate price and service collusion in markets where codeshare partners’ services overlap. I develop a structural econometric model that is able to separately identify supply and demand factors as sources of price-quantity changes caused by the creation of the alliance. The estimates from the model show both collusive and demand increasing effects associated with the codeshare alliance. However, the demand increasing effect is larger than the collusive effect. My second essay considers the effects of the recent Delta/Northwest merger. This merger is of particular interest because the two airlines are codeshare partners. Using pre-merger data, a counterfactual simulation is performed in which Delta and Northwest are assumed to merge. The results indicate that codeshare products owned by the merging firms experience higher predicted price increases relative to pure online products. In addition, the mean predicted price increases are relatively small across most markets. I also examine pre-merger predictions with post-merger data and analysis and find that the pre-merger predictions roughly accord with “de-merger” simulated effects using post-merger data. My third essay takes an extended look at airline mergers. When the Delta/Northwest merger was approved by the Department of Justice, consumer groups and policymakers were concerned that the merger and poor economic outlook would act as a catalyst for more mergers. This paper examines this possible scenario using simulations to model the effects of other codeshare partners merging in addition to Delta and Northwest. Results indicate that the predicted price increases for all mergers exhibit relatively small averages but large variances across markets. Further, the largest predicted price increases affect a small percent of products and an even smaller percent of passengers who choose products owned by a merging firm.
Keywords: codeshare; merger; alliance; airline; pricing; competition; Economics, Commerce - Business (0505); Economics, General (0501)